RANCANG BANGUN KEAMANANAN KENDARAAN MENGGUNAKAN SIDIK JARI DAN GPS TRACKING BERBASIS ARDUINO PADA SEPEDA MOTOR - Teguh Budi Santoso; Gilang Dwi Kurnia (FAKULTAS TEKNIK, 2021)
nnovation in motorcycle technology is increasingly visible from year to year. The increasing number of cases of motorcycle theft in Indonesia seems to be starting to cause significant unrest among motorcycle owners and drivers today. In response to this, Honda provides more security to its motorcycle products by adding a feature known as Secure Key Shutter (SKS). The risk of motorcycle theft is not only at night and in quiet places, during the day and in crowds, thieves can carry out theft of motorized vehicles easily. The theft ofmotor vehicles, especially motorcycles, is a daily problem that still needs to be solved. As for this study, we want to implement a security system in the form of a vehicle motorcycle alarm using fingerprints (Finger Print) and GPS (Global Positioning System) Arduino-based Tracking and this tool functions when a motorcycle vehicle wants to be turned on, the user puts his fingerprint on the finger print to turn it on. the electricity of the motorbike and if the motorbike is lost, it can be tracked using GPS (Global Positioning System) Tracking.